Music Composition Kaliyuga | Komposisi Musik Kaliyuga - Kadek Guntriana; Garwa I Ketut (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Kaliyuga is one of the most recent eras among other Yugas in a cycle of development of the Hindu Religion era in Bali, which is known as Catur Yuga. Kaliyuga is called the Age of Darkness or also known as the Age of Desolation. This creation of percussion is inspired by the negative side of human nature in the Kaliyuga era, in which the human body was filled and controlled by the nature of Adharma. The creator created a creation of percussion work entitled